1993
DOI: 10.1111/j.1744-7348.1993.tb04078.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a low input system for growing wheat (Triticum vulgare) in a permanent understorey of white clover (Trifolium repens)

Abstract: 109 SummaryIn three field experiments carried out during 1989-91, a permanent sward of pure white clover (Trifolium repens) was established to provide a source of N for winter or spring wheat crops (Triticum uulgare) directly drilled into the legume. Spring-sown wheat failed to compete with the clover, but wheat sown in the autumn established successfully. N fertiliser was applied to all three experiments at rates of 0,50 and 100 kg N ha-' and measurements of grain and whole-crop silage yields were made. Yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 13 publications
1
27
2
Order By: Relevance
“…However, compared with studies with strip-band cultivation for wheat seeding (Jones & Clements, 1993;Thorsted et al, 2006b), the present yield results were at the lower range of the reported values. In one trial, the yields of the best varieties were even comparable to organic farming systems with ploughing (4100 kg ha -1 , Maeder et al, 2002).…”
Section: Grain Yieldcontrasting
confidence: 87%
“…However, compared with studies with strip-band cultivation for wheat seeding (Jones & Clements, 1993;Thorsted et al, 2006b), the present yield results were at the lower range of the reported values. In one trial, the yields of the best varieties were even comparable to organic farming systems with ploughing (4100 kg ha -1 , Maeder et al, 2002).…”
Section: Grain Yieldcontrasting
confidence: 87%
“…1). This contrasts with observations of Jones and Clements (1993) and Williams and Hayes (1991) of competition between spring cereals and white clover (Trifolium repens L.) resulting in poor cereal yields. The lack of competition in our study was probably due to the fact that wheat was not established in a perennial stand of clover, but rather seeded simultaneously with it.…”
Section: Discussioncontrasting
confidence: 52%
“…This alternative cropping practice is receiving increasing interest in some temperate (Williams and Hayes 1991;Jones 1992;Jones and Clements 1993;Stute and Posner 1995) and arid regions (Guldan et al 1997). However, to our knowledge, information about the agronomic and environmental aspects of those systems for cold and humid climates as is found in eastern Canada are lacking, despite possible advantages over cereals cultivated in monoculture.…”
mentioning
confidence: 99%
“…Winter wheat yield reductions by red clover are unlikely given that red clover is frost seeded into an established and rapidly growing wheat stand and red clover biomass accumulation during this period is minimal [54,55,69]. Documented negative impacts of clover on wheat growth occurred when wheat was seeded over a permanent perennial understory of white clover [194] where yield reductions are likely due to the competition faced by wheat seedlings in a perennial clover population.…”
Section: Misconception About Effects Of Inter-seeded Red Clover On Cementioning
confidence: 99%